HYGIENIC ANALYSIS OF THE INFLUENCE OF NUTRITION ON HEALTH STATUS OF PRIMARY CLASS STUDENTS (E Global Congress, 2024)
Disruption of daily routines among elementary school students, decrease in the quality of mastery of subjects, deterioration of nutritional status, increase in the number of somatic diseases as a result of the occurrence of alimentary diseases related to nutrition, and specific changes in the promotion of healthy eating habits of schoolchildren are related to the occurrence.According to the information provided by several authors, the number of endemic goiter disease is increasing day by day as a result of the occurrence of iron deficiency anemia and iodine deficiency among schoolchildren[6,7]. Taking this into account, a number of normative and legal documents have been adopted in our country, including the Decree of the President of the Republic of Uzbekistan No. PF-60 of January 28, 2022 "On the Development Strategy of New Uzbekistan for 2022-2026" [1], 4063 of December 18, 2018 - No. "On measures to support the prevention of non-communicable diseases, support a healthy lifestyle and increase the level of physical activity of the population" [2].